KOMPOSISI JENIS DAN TUTUPAN TERUMBU KARANG DI PANTAI SAMUH, NUSA DUA, BALI - Panca Putra, Krisna Jumantara; Arthana, I Wayan; Pratiwi, Made Ayu (Bumi Lestari Journal of Environment, 2022)
Coral reefs are known as very complex and productive ecosystems with a diversity of biota such as mollusks, crustaceans and reef fish. Coral biodiversity, high ecological and economic functions are also accompanied by high threats from various human activities. This study aims to determine the species composition and cover of coral reefs. The research used purposive random sampling method. Data collection at 2 stations with 3 different depths of 3m, 7m, and 10m was carried out using the 1x1 m2 quadrant transect method. The study found 15 types of coral reefs at Samuh Beach including Acropora Baranching (ACB), Acropora Encrusting (ACB), Acropora Submassive (ACS), Acropora Digitate (ACD), Acropora tabulate (ACT), Non-Acropora Baranching (CB), Non-Acropora Acropora Encrusting (CE), Non-Acropora Foliose (CF), Non-Acropora Massive (CM), Non-Acropora Sub Massive (CS), Non-Acropora Mushroom (CMR), Non-Acropora Millepora (CME), Non-Acropora Helliopora (CHL), Soft Coral (SC), Sponge (SP), Zoanthida (ZO), Other (OT). The percentage of Acropora cover was higher than other corals. The highest percentage of coral reef cover is at a depth of 10 m as much as 94.75%, the lowest is at a depth of 3 m as much as 80.66%. Based on the results of the analysis, it was found that the condition of coral reef cover in Samuh Beach was generally classified in the very good and well maintained category.